PENGUATAN MODAL SOSIAL KELEMBAGAAN DALAM PENANGGULANGAN KEMISKINAN PERDESAAN DI PANTAI UTARA DAN PANTAI SELATAN - Mursid Zuhri (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2020)
This study aims to study the social capital role of poor fishermen's activities and to study the social network of fishermen communities and their institutions. This research uses mixed method, namely qualitative and quantitative. The results showed that natural capital in the eleven sample villages is coastal and oceanic, and the majority of the population with formal education has not graduated from elementary school (SD) and low incomes, Smooth interactions between the rulers and laborers are supported by social relationships based on neighborhood, kinship and religious ties, power transfer only occurs in the level of local institutions that is dominated by close groups of power; and there is relatively no social learning process, because the program activities are more economical. The strength of non-material culture or social capital is an important factor in why the people in the eleven sample villages can still survive. The meaning of mutual trust is the result of interactions involving (at least three) community members in a neighboring group, hamlet level associations, village level organizations, and the development of a social network system across village boundaries. (f) Empowerment programs in poverty reduction efforts are influenced by the strength of social capital generated by a number of values ​​(composite) that form networks of mutual trust, mutual respect and mutual benefits.Recommendations that can be given: (a) strengthening social capital such as shame / self-esteem, empathy, honesty, trustworthiness, altruism, being forward-looking and being rational are important; while the driving force for material progress is hard and diligent work, frugal, passionate about innovation, respect for work performance, visionary, and rational. The two combined values, namely for strengthening social capital on the one hand and for driving progress or strengthening material capital on the other hand, collectively (synergistically) are needed in the management of sustainable programs in rural areas. (b) empowerment of rural communities, especially poor fishermen, through strengthening social capital needs to be put in the framework of the transformation or sustainable development of rural communities (c) the development of coastal areas must pay attention to social relations in fishing communities, so as not to lead to social polarization. (d) the factor of village leadership and extension officers is important for the sustainability of an empowerment program in providing guidance for the productive economic business of the fishing community in the form of technical guidance and business management. (e) need post-program “coaching” by the competent agency; (f) the need for empowerment of the poor through increased coordination between poverty alleviation agencies.